2000
DOI: 10.1042/bst0280837
|View full text |Cite
|
Sign up to set email alerts
|

Lipid hydroperoxides in plants

Abstract: Hydroperoxides are the primary oxygenated products of polyunsaturated fatty acids and were determined spectrophotometrically based on their reaction with an excess of Fe2+ at low pH in the presence of the dye Xylenol Orange. Triphenylphosphine-mediated hydroxide formation was used to authenticate the signal generated by the hydroperoxides. The method readily detected lipid peroxidation in a range of plant tissues including Phaseolus hypocotyls (26 +/- 5 nmol.g of fresh weight(-1); mean +/- S.D.), Alstroemeria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The principle of the FOX method is based on the oxidation of ferrous ions to ferric by the hydroperoxide activity in the acidic environment [90][91][92][93][94]. The exact mechanism of the sequence of radical reactions is not known, but the mechanism has been designed by Gupta et al [95] and is shown in reactions 1-4 (equation 2) [96].…”
Section: Ferrous Oxidation In Xylenol Orangementioning
confidence: 99%
“…The principle of the FOX method is based on the oxidation of ferrous ions to ferric by the hydroperoxide activity in the acidic environment [90][91][92][93][94]. The exact mechanism of the sequence of radical reactions is not known, but the mechanism has been designed by Gupta et al [95] and is shown in reactions 1-4 (equation 2) [96].…”
Section: Ferrous Oxidation In Xylenol Orangementioning
confidence: 99%
“…It has the potential to be a rapid and inexpensive method for detecting incipient lipid peroxidation in plant tissue. To our knowledge, the FOX assay has been reported by only one other group for LOOH measurement in plant tissue (31,57), although it has been utilized for LOOH detection in edible vegetable oils (32,33). The main objective of this study was to adapt the FOX assay to more accurately detect the presence of LOOHs in plant tissue.…”
Section: Introductionmentioning
confidence: 99%
“…One to two percent of all membrane phospholipids constantly seem to be present in their peroxidized form. [104] What is the Evidence in Support of the Lipid Scenario?…”
Section: The Concept Of Lipid Noisementioning
confidence: 97%